2022
DOI: 10.1101/2022.12.20.521163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

pGG-PIP: A GreenGate (GG) entry vector collection with Plant Immune system Promoters (PIP)

Abstract: The regulatory sequences controlling the expression of a gene (i.e. the promoter) are essential to properly understand a gene's function. From their use in mutant complementation assays, to studying their responsiveness to different stimuli via transcriptional reporter lines or using them as proxy for the activation of certain pathways, assays using promoter sequences are valuable tools for insight into the genetic architecture underlying plant life. The GreenGate (GG) system is a plant-specific variant of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 96 publications
(85 reference statements)
1
9
0
Order By: Relevance
“…To monitor the infection and colonization of A. thaliana roots by Fo 5176, we cultivated 10-day old seedlings in square petri dishes, added fungal spores and then imaged hyphal growth, infection and colonization over the next 14 days. We used a transgenic Fo 5176 line expressing a cytoplasmic tdTomato fluorophore to visualize the fungus (Calabria et al ., 2022). One of the first things noticeable when imaging infected plants was that the tissue surrounding the colonization site appeared to undergo immediate cell death.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To monitor the infection and colonization of A. thaliana roots by Fo 5176, we cultivated 10-day old seedlings in square petri dishes, added fungal spores and then imaged hyphal growth, infection and colonization over the next 14 days. We used a transgenic Fo 5176 line expressing a cytoplasmic tdTomato fluorophore to visualize the fungus (Calabria et al ., 2022). One of the first things noticeable when imaging infected plants was that the tissue surrounding the colonization site appeared to undergo immediate cell death.…”
Section: Resultsmentioning
confidence: 99%
“…(2018) demonstrated the requirement of the JA-receptor COI1 for PEP1-induced growth inhibition (as an indirect readout for activated immune signaling) and apoplastic ROS-burst via a member of the RBOH family of NADPH oxidases. In our previous work we showed that all of these components, PEP1 , PEPR1 and 2 , BIK1 , and RBOHD , are also locally induced in the vascular cells neighboring the Fo 5176-colonized zone (Calabria et al ., 2022). Of these components, PEP1 and PEPR2 show the strongest induction, with both not just induced in cells of the defense response zone, but also in a long stretch covering the entire region from the HR zone and the defense response zone (Calabria et al ., 2022).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations